Optimizing the Function of Islamic Education within the Family to Prevent Juvenile Delinquency - Pira Tobule Pira; Futy Marwalian Lalio; Kiki Hamrin; Cici Mutia (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Adolescence is a crucial developmental stage characterized by physical, psychological, and socio-economic changes. Islamic religious education plays a strategic role in shaping adolescent character and morals while preventing juvenile delinquency. The family, as the first and foremost educational institution, holds central responsibility for internalizing moral and religious values. However, this process often falls short due to mismatches between educational methods and the psychological characteristics of adolescents, who tend to be critical of authority. Contributing factors to juvenile delinquency within the family include lack of attention, affection, supervision, role modeling, as well as conflict and disharmony. This study employs a library research approach, analyzing various scientific literatures. The findings indicate that optimizing the function of Islamic education through the Islamic Parenting program—encompassing  democratic parenting, role modeling, and advice-based approaches—is effective in cultivating noble character, independence, responsibility, and adolescent awareness of truth values. These three parenting styles must be applied consistently to enable families to create a harmonious, safe, and supportive environment for the positive character development of adolescents.